2008
DOI: 10.1097/jto.0b013e3181653d08
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Management of Lung Cancer in New Zealand

Abstract: Multiple factors are potentially responsible for the higher case-fatality ratio in Mäori. Such factors include presentation with more advanced disease, lower rates of curative treatment for nonmetastatic disease, and longer transit times from diagnosis to treatment. In this retrospective study, socioeconomic deprivation, comorbidity levels, and failure to accept treatment did not fully explain ethnic differences in management. Further assessment of the underlying issues by prospective evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 17 publications
4
49
2
Order By: Relevance
“…Exclusion of these 91 patients yielded an eligible sample of 685. We excluded another 56 patients (equal numbers of Maori and non-Maori individuals) who had missing information on key variables, including date of diagnosis, 26 tumor histology, 17 tumor site and/or grade, 9 and key demographic data. 4 The final study cohort (n ¼ 629) represented 92% of all eligible individuals and comprised 301 Maori patients and 328 non-Maori patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion of these 91 patients yielded an eligible sample of 685. We excluded another 56 patients (equal numbers of Maori and non-Maori individuals) who had missing information on key variables, including date of diagnosis, 26 tumor histology, 17 tumor site and/or grade, 9 and key demographic data. 4 The final study cohort (n ¼ 629) represented 92% of all eligible individuals and comprised 301 Maori patients and 328 non-Maori patients.…”
Section: Resultsmentioning
confidence: 99%
“…Survey data indicate that Maori New Zealanders are more likely to report having experienced discrimination from health professionals on the basis of their ethnicity. 43 Evidence from the United States suggests that interpersonal discrimination contributes to ethnic disparities in care, 7,9 but treatment inequities there are driven more by differences between healthcare providers than by differential care within the same facility. 35,37,42 The balance of these factors may be somewhat different in New Zealand, where ethnic segregation is less marked than in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Yet both recent studies of cancer treatment found Māori patients received lower rates of curative intervention even after adjustment for co-morbidity. 25,26 Co-morbidity is not necessarily a contraindication to treatment such as chemotherapy, which confers significant survival advantage even in the presence of pre-existing medical conditions. 32,33 Withholding potentially curative treatment in the presence of co-morbidity will disproportionately disadvantage groups with higher levels of coexisting disease.…”
Section: Patient Factorsmentioning
confidence: 99%
“…18 Two recent studies show Māori are less likely than European patients to receive curative treatment for cancer of the lung and colon. 25,26 Stevens et al reviewed management of lung cancer in a cohort of patients diagnosed and treated in Auckland and Northland in 2004. 25 They found Māori patients were significantly less likely than Europeans to receive potentially curative treatment (received by 12% of Māori compared with 22% of European patients).…”
Section: Inequalities In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation